Interventions to reduce cognitive impairments following critical illness: a topical systematic review. Issue 2 (22nd November 2016) - Nedergaard, H. K.; Jensen, H. I.; Toft, P.
Abstract : Background: Critical illness is associated with cognitive impairments. Effective treatment or prevention has not been established. The aim of this review was to create a systematic summary of the current evidence concerning clinical interventions during intensive care admission to reduce cognitive impairments after discharge. Methods: Medline, Embase, Cochrane Central, PsycInfo and Cinahl were searched. Inclusion criteria were studies assessing the effect of interventions during intensive care admission on cognitive function in adult patients. Studies were excluded if they were reviews or reported solely on survivors of cardiac arrest, stroke or traumatic brain injury. Results: Of 4877 records were identified. Seven studies fulfilled the eligibility criteria. The interventions described covered strategies for enteral nutrition, fluids, sedation, weaning, mobilization, cognitive activities, statins and sleep quality improvement. Data were synthesized to provide an overview of interventions, quality, follow‐up assessments and neuropsychological outcomes. Conclusion: None of the interventions had significant positive effects on cognitive impairments following critical illness. Quality was negatively affected by study limitations, imprecision and indirectness in evidence. Clinical research on cognition is feasible, but large, well designed trials with a specific aim at reducing cognitive impairments are needed.